BARRIERS AND ACCESS TO MENTAL HEALTHCARE IN RURAL AREAS OF PAKISTAN: AN INFERENTIAL STATISTICAL ANALYSIS - Kinza Riaz; Muhammad Sajid; Muhammad Ishtiaq; Humera Amin (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Mental healthcare accessibility remains a significant challenge in rural Pakistan, where services are limited, and socio-cultural barriers, including stigma, further hinder utilization. This study investigates these barriers and explores factors influencing access to mental healthcare services in rural areas. Objectives: The study aims to: 1) assess the availability and accessibility of mental healthcare services; 2) examine mental health awareness levels; 3) identify socio-cultural and economic barriers; and 4) estimate the association between demographic factors and access to mental healthcare. Methodology: A cross-sectional survey design was employed, collecting data from 500 respondents in rural Pakistan using a structured questionnaire. Stratified random sampling was used to ensure representativeness. Analytical techniques such as chi-square tests, logistic regression, ANOVA, and Pearson correlation were applied to examine associations between variables, including income, education, and stigma. Results: Only 28% of respondents reported local availability of mental healthcare services, with 78% lacking access to mental health professionals. Travel distances, long waiting times, and high costs were identified as significant barriers. Stigma was pervasive, with 38% of respondents reporting strong stigma, and 64% avoiding treatment. Logistic regression showed that higher income and education significantly increased the likelihood of accessing mental healthcare, while stigma reduced utilization. Conclusion: The study underscores the urgent need for mental healthcare infrastructure expansion, targeted awareness campaigns, and telehealth services in rural Pakistan. Addressing socio-cultural stigma and affordability issues is essential for improving mental health outcomes in these communities.